UKURAN PERUSAHAAN, PROFITABILITAS, RISIKO BISNIS YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR - Veronika , Lien Putri; Sudirgo, Tony (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This study aims to determine whether company size, profitability and business risk affect the capital structure of manufacturing companies listed on the Indonesia Stock Exchange during 2019-2021. The population used in this study is all manufacturing companies on the Indonesia Stock Exchange of 166 companies. The sample determination technique used is the purposive sampling method and the valid data is 60 companies. The data processing techniques used are multiple regression analysis assisted by the software programs Eviews 12 for Windows released 20 and Microsoft Excel for Microsoft 365 MSO.The results of the research that has been carried out the size of the company have a significant influence on the capital structure. Profitability and business risk have no effect on the capital structure. The implication of this research is that companies need to increase the effect of funding on the capital structure for each company.